Perancangan dan Implementasi Sistem Penerimaan Peserta Didik Baru (SPMB) Berbasis Web pada Sekolah Unggulan - Muhammad Yunus Rangkuti; Yanuar Nurfirgiansyah; Andika Wiranata; Muhamad Qosim Nur Abid (Jurnal Riset Informatika dan Inovasi, 2026)
The student admission process (SPMB) is a crucial stage in educational management at schools. Manual admission procedures often cause various problems, such as delays in data processing, recording errors, and limited transparency of information for prospective students and parents. This study aims to design and implement a web-based student admission system at a Superior School to improve efficiency, effectiveness, and the quality of registration services. The research method applied is a system development approach consisting of requirement analysis, system design, implementation, and testing stages. The results show that the web-based SPMB system is able to facilitate online registration, provide academic information, and manage prospective student data in a structured and integrated manner. This system is expected to support school administrators in decision-making processes and to provide easy access to information for the public.